The correlation between the fracture induced acoustic emission and the compressive static strength in plain and high strength concrete - MIERZWA, J.; POGAN, K.; RANACHOWSKI, Z. (Archives of Acoustics, 1997)
In this article Acoustic Emission (AE) measurement results for six different concrete compositions, differing in compressive strength, are presented. The aim of the investigation was to find the dependence between the mechanical strength and the count sum of the registered Acoustic Emission. AE signals were measured by a quasi-axial compression test. Two acoustical parameters were examined and compared with the compressive strength and static strength of the compositions tested. The first one was the AE activity during the complete compression process and the second one was the AE activity measured to the point of the start of the instable crack growth propagation process.